2019
DOI: 10.5513/jcea01/20.2.2005
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of the Western corn rootworm, Diabrotica virgifera virgifera larvae caused by entomopathogenic fungi

Abstract: Mortality of the Western corn rootworm (WCR) larvae caused by entomopathogenic fungi Beauveria bassiana, Beauveria brongniartii, Metarhizium anisopliae was investigated in a laboratory. Larvae were treated with a spore suspension (concentration of 2 x 10 7 conidia/ml) by immersion. Only one strain of entomopathogenic fungi, a strain of B. brongniartii, significantly influenced mortality of WCR larvae after 7 days. Average mortality of the larvae was 17.63%. After 14 days, five strains of B. bassiana, two strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
1
0
0
Order By: Relevance
“…Biological control with pathogens and nematodes offers a different outlook, with several promising laboratory and greenhouse results. Several strains of Beauveria bassiana, B. brongniartii (Hypocreales: Cordycipitaceae), and Metarhizium anisopliae (Hypocreales: Clavicipitaceae) were effective in controlling Diabrotica virgifera virgifera larvae for up to 21 days after application [110]. Similar results have been obtained for South American species.…”
Section: Biological Controlsupporting
confidence: 72%
“…Biological control with pathogens and nematodes offers a different outlook, with several promising laboratory and greenhouse results. Several strains of Beauveria bassiana, B. brongniartii (Hypocreales: Cordycipitaceae), and Metarhizium anisopliae (Hypocreales: Clavicipitaceae) were effective in controlling Diabrotica virgifera virgifera larvae for up to 21 days after application [110]. Similar results have been obtained for South American species.…”
Section: Biological Controlsupporting
confidence: 72%
“…Testing twenty strains of B. bassiana, B. brongniartii (Saccardo) Petch and M. anisopliae at a concentration of 1 × 10 7 conidia/ml against larvae and adults of WCR in the laboratory Pilz et al (2007) reported that isolates of M. anisopliae caused significantly higher mortalities than isolates of B. brongniartii and B. bassiana. Similarly, 21 days after inoculation, a strain of M. anisopliae (MA1) caused higher mortality of the WCR larvae than the strains of B. bassiana and B. brongniartii, all strains were tested at a concentration of 2 × 10 7 conidia/ml (Cagáň et al, 2019).…”
Section: Discussionmentioning
confidence: 99%